2020
DOI: 10.1093/mnras/staa2339
|View full text |Cite
|
Sign up to set email alerts
|

A multiwavelength search for black widow and redback counterparts of candidate γ-ray millisecond pulsars

Abstract: The wealth of detections of millisecond pulsars (MSPs) in γ-rays by Fermi has spurred searches for these objects among the several unidentified γ-ray sources. Interesting targets are a sub-class of binary MSPs, dubbed ”Black Widows” (BWs) and ”Redbacks” (RBs), which are in orbit with low-mass non-degenerate companions fully or partially ablated by irradiation from the MSP wind. These systems can be easily missed in radio pulsar surveys owing to the eclipse of the radio signal by the intra-binary plasma from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Wang et al (2020) suggested that follow-up observations be conducted to determine if the binary is in fact a transitional MSP in an accretion-driven state or, potentially, the rotationally-powered MSP state that would follow. Braglia et al (2020) also reported two new spider candidates in a similar fashion. By searching for optical variations in archival survey data for systems that had possible associated X-ray counterparts within the Fermi uncertainty region, they identified 4FGL J1627.7+3219 and 4FGL J2212.4+0708 as candidates.…”
Section: Introductionmentioning
confidence: 73%
“…Wang et al (2020) suggested that follow-up observations be conducted to determine if the binary is in fact a transitional MSP in an accretion-driven state or, potentially, the rotationally-powered MSP state that would follow. Braglia et al (2020) also reported two new spider candidates in a similar fashion. By searching for optical variations in archival survey data for systems that had possible associated X-ray counterparts within the Fermi uncertainty region, they identified 4FGL J1627.7+3219 and 4FGL J2212.4+0708 as candidates.…”
Section: Introductionmentioning
confidence: 73%
“…In fact, three of our targets, 1FGL J0523.5−2529 (Strader et al 2014), 1FGL J1119.9 −2205 (Swihart et al 2022b), and 1FGL J1544.5−1127 (Strader et al 2019), have been suggested to be redbacks through the identification of a plausible optical counterpart. PSR J0955−3947, another redback candidate (Braglia et al 2020), was recently confirmed as a short-orbit pulsar by TRAPUM 29 (Clark et al 2023a).…”
Section: Implications For γ-Ray Pulsar Population Statisticsmentioning
confidence: 95%
“…In particular, the distribution of unassociated Fermi sources in galactic latitude suggests a likely Galactic origin for a significant fraction of the 2600 unidentified sources. While a significant fraction of these low-latitude sources may originate from mismodeled diffuse emission (Abdollahi et al 2022), it is a promising effort to search for new pulsars in individual unassociated Fermi sources, as numerous previous studies have shown (e.g., Au et al 2023;Bruzewski et al 2023;Hare et al 2022;Braglia et al 2020).…”
Section: Introductionmentioning
confidence: 99%